How prolonged is a prolonged disorder of consciousness? Longterm follow-up of 71 consecutive admissions. Issue 6 (27th May 2022) - Allanson, Judith; Holland, Tony; Pickard, John; Kamau, Evelyn; Bareham, Corinne; Roberts, Neil; Stamatakis, Emmanuel; Menon, David; Hutchinson, Peter; Barclay, Stephen
Abstract : There is little Uk data on outcome after Prolonged Disorders of Consciousness(PDOC) and yet, in the light of recent case law and professional guidelines, this is essential for reliable prognostication and thus for best interests discussions about provision of clinically assisted nutrition and hydration. This study reports the very longterm outcome of 69/71 consecutive admissions to a UK fMRI study of PDOC after brain injury. (mean age 47y; 52 male; initially seen at mean 20 m post injury; 47 traumatic brain injury, 18 hypoxia). Status of those alive at follow up (mean 8y7m post injury) was determined after direct examination or use of the Coma-recovery-scale-revised telephone version, with clinicians and families. Mortality data revealed 33/71 (47%) had died naturally at mean of 55m post injury; mean age 49y; this included 27/50 of those initially in Vegetative or Minimally Conscious minus; 21/47 with TBI. Of note 13/69 (19%) who had not emerged at first assessment had recovered to emergence or higher level at followup. 11 were fully active; eg snow-boarding. One regained speech 5 years after injury. 11 were living in domestic settings; 9 with care packages. Only 2/11 with evidence of covert awareness on initial fMRI had emerged. Although these data are from a very selected cohort this data reveals recovery from PDOC can occur very late after injury in those confirmed to be in PDOC after detailed clinical assessment. judith.allanson.1@gmail.com